A review on the identification of transgenic oilseeds and oils - Pan, Pengyuan; Xing, Yihang; Zhang, Dingwen; Wang, Ji; Liu, Chunlei; Wu, Dan; Wang, Xiyan (Journal of food science, 2023)
Transgenic technology can increase the quantity and quality of vegetable oils worldwide. However, people are skeptical about the safety of transgenic oil‐bearing crops and the oils they produce. In order to protect consumers’ rights and avoid transgenic oils being adulterated or labeled as nontransgenic oils, the transgenic detection technology of oilseeds and oils needs careful consideration. This paper first summarized the current research status of transgenic technologies implemented at oil‐bearing crops. Then, an inspection process was proposed to detect a large number of samples to be the subject rapidly, and various inspection strategies for transgenic oilseeds and oils were summarized according to the process sequence. The detection indicators included oil content, fatty acid, triglyceride, tocopherol, and nucleic acid. The detection technologies involved chromatography, spectroscopy, nuclear magnetic resonance, and polymerase chain reaction. It is hoped that this article can provide crucial technical reference and support for staff engaging in the supervision of transgenic food and for researchers developing fast and efficient monitoring methods in the future.